Canada and the International Labour Organization in the Interwar Period, 1919-1940 - Hucul, Jeffrey Gordon (University of Windsor, 1984)
In 1919, Canada, by virtue of its central role in the conduct of World War I, took its place as a member of the international community in the League of Nations and in the first representative body for world labour, the International Labour Organization. This thesis examines Canada's relations with the I.L.O. in the interwar period (1919-1940). It is hypothesized that Canada's role in the I.L.O. in this period reflected not the concerns and ideals of the organization per se, but rather the political and constitutional goals of the Dominion government. Consequently, social reform in Canada, as implied in the principles of the constitution of the I.L.O., was usually of secondary importance to the governments of Canada during this period, and especially to Canadian industry, which were often united in thwarting the efforts of Canadian labour and the I.L.O. to influence social reform in Canada. Indeed, both Canadian governments and industry, came to recognize in the constitutional issue a useful vehicle to slow down the pace of social reform during this period....